TREATMENT OF PROLONGED NEONATAL JAUNDICE - T.I. Kaganova; A.A. Loginova ("Paediatrician" Publishers LLC, 2011)
In the past decade we have witnessed a dramatic increase in the incidence of prolonged neonatal hyperbilirubinemia. The reason for that is still unknown. Neither there're any standardised guidelines for treatment of infants with prolonged jaundice. The article contains results of the literature review related to methods of treatment of neonatal prolonged hyperbilirubinemia.Key words: neonates, hyperbilirubinemia, jaundice, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 137-140)